HACE1 deficiency causes an autosomal recessive neurodevelopmental syndrome. Issue 12 (30th September 2015) - Hollstein, Ronja; Parry, David A; Nalbach, Lisa; Logan, Clare V; Strom, Tim M; Hartill, Verity L; Carr, Ian M; Korenke, Georg C; Uppal, Sandeep; Ahmed, Mushtaq; Wieland, Thomas; Markham, Alexander F; et al.
Abstract : Background: The genetic aetiology of neurodevelopmental defects is extremely diverse, and the lack of distinctive phenotypic features means that genetic criteria are often required for accurate diagnostic classification. We aimed to identify the causative genetic lesions in two families in which eight affected individuals displayed variable learning disability, spasticity and abnormal gait. Methods: Autosomal recessive inheritance was suggested by consanguinity in one family and by sibling recurrences with normal parents in the second. Autozygosity mapping and exome sequencing, respectively, were used to identify the causative gene. Results: In both families, biallelic loss-of-function mutations in HACE1 were identified. HACE1 is an E3 ubiquitin ligase that regulates the activity of cellular GTPases, including Rac1 and members of the Rab family. In the consanguineous family, a homozygous mutation p.R219* predicted a truncated protein entirely lacking its catalytic domain. In the other family, compound heterozygosity for nonsense mutation p.R748* and a 20-nt insertion interrupting the catalytic homologous to the E6-AP carboxyl terminus (HECT) domain was present; western blot analysis of patient cells revealed an absence of detectable HACE1 protein. Conclusion: HACE1 mutations underlie a new autosomal recessive neurodevelopmental disorder. Previous studies have implicated HACE1 as a tumour suppressor gene; however, since cancer predisposition was not observed either in homozygous or heterozygous mutation carriers, this concept may require re-evaluation.